Models and Algorithms for Global Optimization Essays Dedicated to Antanas Žilinskas on the Occasion of His 60th Birthday - Törn, Aimo; Žilinskas, Julius (Springer Optimization and Its Applications, 2007)
The research of Antanas Žilinskas has focused on developing models for global optimization, implementing and investigating the corresponding algorithms, and applying those algorithms to practical problems. This volume, dedicated to Professor Žilinskas on the occasion of his 60th birthday, contains new survey papers in which leading researchers from the field present various models and algorithms for solving global optimization problems. Audience This book is intended for scientists and graduate students in computer science and applied mathematics who are interested in optimization algorithms and numerical analysis.